Differential use of multiple food sources at a bathyal benthic ecosystem in the central Sagami Bay revealed by amino acid nitrogen isotopic compositions - Hidetaka Nomaki; Yoshito Chikaraishi; Nanako O. Ogawa; Koh Maki; Motohiro Shimanaga; Hisami Suga; Masashi Tsuchiya; Toshi Nagata; Naohiko Ohkouchi (Progress in Earth and Planetary Science)
Abstract The nitrogen isotopic composition (δ 15N) of amino acids can be used to estimate the trophic position of organisms with high precision compared to bulk tissue analyses, and shed light on potential food sources and food webs. Sagami Bay, Japan, is located at the tectonic plate boundary and have complex bottom topography, making multiple sources of organic matter to bathyal deep-sea ecosystems. Here, we applied this method to benthic animals (meiofauna, macrofauna, and megafauna) living at 1430 m deep in the central Sagami Bay, Japan. The δ 15N value of phenylalanine (δ 15NPhe) reflects the value of primary producers and was used to estimate the food sources of organisms, while the difference between δ 15N value of glutamic acid (δ 15NGlu) and δ 15NPhe shifts between food source and consumer and was thus used to estimate the trophic position (TPGlu/Phe). The data obtained were interpreted together with previously reported values from benthic foraminifera of the same site for a holistic understanding of the food web. The trophic positions of organisms from the central Sagami Bay ranged mostly from 2.2 to 3.6, except hydrozoans (up to 4.3). Organisms with similar bulk tissue δ 15N values sometimes exhibited different TPGlu/Phe values. The observed δ15NPhe varied greatly among benthic organisms in the central Sagami Bay (− 8.3‰ to 21.1‰), suggesting a wide variety of food sources exhibiting different δ15NPhe values. Given the location of the study site at the central part of the deep basin, various organic matter from terrestrial, planktic, coastal, upper bathyal, and perhaps chemosynthetic origins can be expected to accumulate and become available for bathyal benthic organisms. Furthermore, the cross-plot of δ15NPhe values and bulk tissue δ 13C values, another indicator of food source, suggested that macro–megafauna examined rely on different organic matter than metazoan meiofauna and foraminifera, which rely on particulate organic matter and bulk sediments. Despite living in the same habitat, organisms of these two size classes may belong to independent food webs due to differences in feeding ecology.